PARTISIPASI LEMBAGA UNIT EKONOMI DESA – SIMPAN PINJAM ( UED – SP ) KAYU BEIMBAI DESA TELUK BUNIAN KABUPATEN INDRAGIRI HILIR DALAM PEMBERDAYAAN EKONOMI MASYARAKAT ) - ", Saban (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Institutions of economic unit village savings and loans ( EUD – SP ) beimbai timber bay village districts bunian pelangeran kabupaten Indragiri downstream are microfinance institutions ( MFIS) which is in the form of the village / village though consensus to manage the funds of rural enterprises ( DUD ) and funds derived of the activities of savings and loan society beimbai wood bunian.ada bay village was doing agency business in the economic unit village savings and loans ( UED – SP ) beimbai timber bay village bunian is managing the funds of rural enterprises and lending money to people who do business either indivudually economy or even in groups. as an institutions – based community empowerment such as savings and loan institution economy unit village / village savings and loans ( UED – SP ) paddle beimbai bay village bunian become a frontline in helping economic enterprise communities for more admanced and independentin achieving welfare, also has the function to economic empowerment of the poor so that they com out for the vicious circle of poverty. Based on the phenomenon and the writer’s observation regarding the institutions of economic unit village savings and loans ( UED – SP ) beimbai wood bunian bay village has a strategic role in assisting the process of economic improvement masyarakat.melalui economic empowerment in order to achieve the goal of making the community development seutuhnya.and achieve the ideals bunian bay village districts downstream pelangeran Indragiri districts in improving the welfare of society.Keywords: Institutions savings and loans helping economic